Nationalisme et littérature au cours de la renaissance acadienne (1864-J930). Voix discordantes - Guérin, Pierre M. (Studia Romanica Posnaniensia, 2017)
This article examines a key event in the literary history of the Acadian renaissance (1864-1930), the founding of newspapers. Our study deals specifically with the status given to literary works in newspapers. In sequence, we will look at Marichette's Lettres (1895-1898) published in L'Évangéline, the novel Placide, l'homme mystérieux by Paul (1904-906) published in L'Impartial and the play « Subercase » (1902, 1936) published in Le Moniteur acadien